Nano silicon material with solid aluminum solution and preparation method thereof and application as negative electrode material for lithium secondary battery
By using solid-solved aluminum nanosilicon materials in lithium-ion batteries and preparing by smelting and rapid cooling, the problem of silicon-based anode material rupture due to lattice expansion during circulation is solved, and the process is simplified and the cost is reduced, achieving efficient electrochemical performance.
Patent Information
- Application Number
- CN202410394849.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-02
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-04-02
AI Technical Summary
The silicon-based anode material in lithium-ion batteries is prone to rupture due to lattice expansion during the charge and discharge cycle, resulting in instability of the electrode interface and loss of electrical contact, affecting its cycle life; at the same time, the preparation process of existing nano-silicon is complex and costly.
A refined aluminum-silicon two-phase eutectic alloy is prepared by melting and rapid cooling, and the metal aluminum phase is removed by dealloyment to obtain a nano-silicon material of solid-solved aluminum. By changing the cooling method or speed, the solid solution of aluminum elements is controlled, and the conductivity and electrochemical properties of silicon materials are improved.
Lithium-ion battery negative electrode material with high first-time Coulomb efficiency, specific capacity and cycle life is achieved, while simplifying the preparation process and reducing costs.
Smart Images

Figure CN118183751B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of lithium ion battery materials, and in particular relates to a silicon-based negative electrode material for lithium ion batteries and a preparation method thereof. Background Art
[0002] Lithium-ion batteries (LIBs) are widely used in various mobile devices. Silicon has an ultra-high lithium storage capacity (3579 mA h / g) and a low working potential (370 mV Vs. Li+ / Li). Replacing the existing graphite negative electrode can greatly improve the energy density of LIBs, and it is not easy to precipitate lithium and has good safety. However, the transition from Si (battery discharge state) to Li 15 Si 4 The inherent ~380% lattice expansion (in the battery charging state) makes silicon particles prone to cracking / crushing, electrode interface instability and electrical contact loss during the charge and discharge cycle, seriously affecting its cycle life. Nanosizing the size of silicon crystals can greatly alleviate the stress caused by cycling and inhibit the cracking of silicon primary particles.
[0003] However, nano-silicon will face two major problems in practical application: First, silicon is a semiconductor, and its conductivity (10 -5 S / cm) is much lower than graphite (10 3 S / cm), which will lead to a large voltage polarization during the electrochemical lithium insertion and extraction process, and easily lead to the formation of "dead silicon", which deteriorates the reversibility of lithium insertion and extraction of the material within a specific voltage range, and the coulombic efficiency and cycle life are not high; secondly, the existing nano-silicon preparation process either requires the use of expensive and hazardous silane gas (vapor deposition method) or the use of complex, labor-intensive and time-consuming multi-stage nano-sand grinding (sand grinding method), resulting in high process costs for nano-silicon, which greatly limits the development and application of silicon-based negative electrode materials. Therefore, it is of great practical application value to develop large-scale, low-cost synthesis methods to prepare nano-silicon materials with high electronic conductivity. The preparation of nano-silicon materials with high first coulombic efficiency and improved conductivity is expected to be promoted to the field of practical application. Summary of the invention
[0004] The purpose of the present invention is to address the above-mentioned problems existing in the prior art and to provide a nano-silicon material with solid-solution aluminum, a preparation method thereof, and an application thereof as a negative electrode material for lithium secondary batteries, so as to obtain a silicon negative electrode material for lithium-ion batteries having high initial coulombic efficiency, high specific capacity and high conductivity, while simplifying the preparation process and significantly reducing costs.
[0005] The main idea of the present invention is to prepare a refined aluminum-silicon two-phase eutectic (quasi-eutectic) alloy by a smelting and rapid cooling method, and then remove the metal aluminum phase by a dealloying method to obtain a nano-silicon material. Since the melting and casting processing conditions are far from the thermodynamic equilibrium state, a certain amount of aluminum solid solution exists in the silicon material obtained at this time, and the aluminum solid solution can play a doping modification role and greatly improve the intrinsic electronic conductivity of the silicon material. By changing the rapid cooling method or speed, the nano-sizing degree of silicon can be controlled and different concentrations of aluminum solid solution can be formed in the bulk phase, thereby improving the conductivity of silicon and the reversibility of electrochemical lithium insertion and extraction, and finally obtaining a high-performance aluminum solid solution nano-silicon material. As a negative electrode material for lithium-ion batteries, the aluminum solid solution nano-silicon can effectively reduce the formation of "dead silicon" compared to traditional nano-silicon, thereby obtaining a higher first coulomb efficiency, specific capacity and cycle life.
[0006] The method for preparing the nano silicon material of solid solution aluminum provided by the present invention comprises the following contents:
[0007] (1) preparing a rapidly cooled aluminum-silicon alloy by one of the rapid cooling methods such as aerosol granulation, liquid nitrogen rapid cooling, centrifugal disk spray, and belt rapid cooling, wherein the mass proportion of the aluminum phase is 50-95%;
[0008] (2) After the quenched aluminum silicon alloy is fully dispersed in the solvent L1, an antioxidant is added and dispersed, and then an acid etchant is added and continuously stirred to react to obtain a precursor mixed solution S1;
[0009] (3) S1 is subjected to solid-liquid separation, washing and solid collection to obtain precursor S2;
[0010] (4) The precursor S2 is dried to obtain a solid solution aluminum nano-silicon material.
[0011] In the above method, further, steps (1) to (4) are respectively as follows:
[0012] (1) Aluminum ingots and silicon ingots with a purity of 99.99% are fully melted at a mass ratio of (50-95):(50-5) above the melting point of silicon (1414°C), and then the alloy liquid is rapidly cooled by one of the rapid cooling methods such as aerosol granulation, liquid nitrogen quenching, centrifugal disk spraying, and belt quenching to refine the grains and simultaneously dissolve aluminum to obtain a rapidly cooled aluminum-silicon alloy powder;
[0013] (2) Dispersing the quenched aluminum silicon alloy powder in the solvent L1 to obtain a mixed solution A, and then adding an antioxidant to the mixed solution A to obtain a mixed solution B, wherein the mass ratio of the antioxidant to the quenched aluminum silicon alloy is (0-0.3):1; adding an acid etchant dropwise into the solvent L1 to obtain a mixed solution C; mixing the mixed solution C and the mixed solution B evenly, and controlling the mass ratio of the quenched aluminum silicon alloy powder and the acid etchant to control the degree of removal of the metal aluminum phase and the degree of oxidation of silicon, wherein the mass ratio of the quenched silicon alloy to the acid etchant is 1:(3-15), and the concentration of the acid etchant in the obtained mixed solution is controlled to be 15%-30%, and then continuously stirring the reaction for 3-30 h to obtain a completely etched precursor mixed solution S1;
[0014] (3) The precursor solution S1 is subjected to solid-liquid separation, and is repeatedly washed with solvent L2 until the pH is greater than 6 to obtain a wet material precursor S2;
[0015] (4) Dispersing the wet material precursor S2 in the solvent L3 to obtain a mixed solution D, and drying the mixed solution D to obtain a solid solution aluminum nano-silicon material.
[0016] In the above method, further, the quenched silicon alloy powder obtained in step (1) is sieved and then selected to obtain a particle size D 50 =6~80μm.
[0017] In the above method, further, in step (2), the solvent L1 is a mixed solution of ethanol and deionized water, wherein the volume fraction of deionized water is 60-100%; the mass ratio of the quenched silicon alloy powder and the solvent L1 in the mixed solution A is 1:(5-50); the dispersion method is a combination of one or more of stirring and ultrasound, and the dispersion time is 0.5-10 h.
[0018] In the above method, further, the antioxidant in step (2) is one or a combination of sodium sulfite, ascorbic acid, isoascorbic acid, sodium ascorbate, sodium isoascorbate; the acid etchant is one or a combination of phosphoric acid, hydrochloric acid, sulfuric acid, oxalic acid, boric acid; and the mass concentration of the acid etchant in the mixed solution C is 10% to 40%.
[0019] In the above method, further, the solid-liquid separation method described in step (3) is one or a combination of filter press, suction filtration, differential centrifugation, density gradient centrifugation, and sedimentation centrifugation; wherein the solvent L2 is a deionized water solution of ethanol, wherein the volume dispersion of deionized water is 60~100%.
[0020] In the above method, further, the dispersion method in step (4) is a combination of one or more of stirring and ultrasound, and the dispersion time is 0.5 to 10 h; the drying method is a combination of one or more of forced air drying, vacuum drying, freeze drying, and natural evaporation drying; the solvent L3 is an ethanol deionized water solution, wherein the volume fraction of water is 60 to 100%; and the solid content of the mixed solution D is 20% to 60%.
[0021] The nano-silicon material with solid-solution aluminum prepared by the above method provided by the present invention preferably has a solid-solution aluminum phase content of 2-10%, preferably 2-8%, and a particle size of 30-100 nm.
[0022] The solid-solution aluminum nano-silicon material provided by the present invention is used as a negative electrode material for a lithium-ion secondary battery.
[0023] Preferably, the application is to mix nano silicon, conductive agent and adhesive in a certain ratio (refer to the conventional preparation method in the art) to obtain slurry, and then evenly coat the slurry on copper foil and dry it to obtain electrode sheet material. When in use, it can be cut into the required shape.
[0024] The invention provides an application of the solid-solution aluminum nano-silicon material as a precursor for preparing silicon-based composite electrode active materials for lithium-ion secondary batteries.
[0025] The application is specifically to mix the solid-solution aluminum nano-silicon material with precursors such as carbon materials, polymer materials and metal materials, solid / liquid phase reaction, sintering, etc. to prepare a silicon-based composite negative electrode active material for lithium-ion batteries.
[0026] Further preferably, the application is as a precursor for preparing silicon-carbon negative electrode materials for lithium-ion secondary batteries.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] 1. The solid-solution aluminum nano-silicon prepared by the method of the present invention can control the solid-solution amount of aluminum in the silicon phase by changing the quenching method or speed (different cooling methods correspond to different cooling speed ranges, and the quenching speed is selected and controlled by selecting different quenching methods) to achieve different concentrations of metal aluminum solid solution, thereby greatly improving the battery performance of silicon materials. At the same time, the silicon size is refined by increasing the cooling speed, and the silicon has a high degree of nano-sizing, which prevents silicon particles from cracking and pulverizing during the lithium insertion and extraction cycle. The structural stability is good, which helps to further improve its coulomb efficiency and electrochemical performance. The application of silicon-based negative electrode materials in lithium secondary batteries has the effect of increasing battery energy density and reducing watt-hour costs.
[0029] 2. The alloying, dealloying, washing, drying and other processes adopted by the method of the present invention are simple, efficient and safe, have low equipment requirements, and do not use expensive and high-risk raw materials. Compared with the nano-silicon prepared by the current sand milling or CVD method, not only the performance is improved, but also the preparation cost, process time and scalability have significant advantages. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a SEM scanning electron microscope image of the solid solution aluminum nano-silicon negative electrode material 1 prepared in Example 1;
[0031] Figure 2 TEM transmission electron microscope-energy dispersive X-ray spectrometer EDS element distribution diagram of the solid solution aluminum nano-silicon negative electrode material 1 prepared in Example 1;
[0032] Figure 3 The charge and discharge curve of the solid solution aluminum nano-silicon negative electrode 1 prepared in Example 1 at a current density of 100 mA / g;
[0033] Figure 4 is the X-ray diffraction pattern of the solid solution aluminum nano-silicon negative electrode material 2 prepared in Example 2;
[0034] Figure 5 This is a SEM scanning electron microscope image of the solid solution aluminum nano-silicon negative electrode material 2 prepared in Example 2;
[0035] Figure 6 The charge and discharge curve of the solid solution aluminum nano-silicon negative electrode 2 prepared in Example 2 at a current density of 100 mA / g;
[0036] Figure 7 The cycle curve of the solid solution aluminum nano-silicon negative electrode 2 prepared in Example 1 at a current density of 500 mA / g;
[0037] Figure 8 The charge and discharge curve of the nano-silicon negative electrode in Comparative Example 1 at a current density of 100 mA / g;
[0038] Fig. 9 Comparison of (111) crystal plane X-ray diffraction patterns and 2θ and lattice constants of the solid solution aluminum nano-silicon material 1 prepared in Example 1, the solid solution aluminum nano-silicon material 2 prepared in Example 2, and the nano-silicon material of Comparative Example 1.
[0039] Fig.10 These are curves showing the change in conductivity of the solid-solution aluminum nano-silicon material 1 prepared in Example 1, the solid-solution aluminum nano-silicon material 2 prepared in Example 2, and the nano-silicon material in Comparative Example 1 as a function of pressure. DETAILED DESCRIPTION
[0040] The present invention is further explained below in conjunction with specific examples. It is necessary to point out that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Those skilled in the art in this field can make some non-essential improvements and adjustments to the present invention based on the above invention content.
[0041] In the following examples, the percentage concentrations of the ethanol aqueous solutions used are all volume concentrations.
[0042] Example 1
[0043] (1) Aluminum ingots with a purity of 99.99% and silicon ingots were fully melted at 1600°C in a ratio of 88:12, and then the alloy liquid was rapidly cooled by aerosol granulation to refine the grains and dissolve aluminum at the same time, and D was selected by screening. 50 =8 μm powder.
[0044] (2) Ultrasonic dispersion of 20 g of the above-mentioned quenched aluminum-silicon alloy powder in 100 ml of water, ultrasonically treating at 100 Hz power for 1 h and stirring at 100 rpm for 1 h to obtain a mixed solution A, and then adding ascorbic acid to the mixed solution A to obtain a mixed solution B, wherein the ratio of ascorbic acid to the quenched aluminum-silicon alloy powder is 0.1:1; 240 g of 85 wt% phosphoric acid is dropwise added to 300 ml of 10 vol% ethanol water to obtain a mixed solution C, wherein the mass ratio of the quenched silicon alloy to the acid etchant is 1:10; C is poured into B to obtain a mixed solution, the concentration of phosphoric acid is controlled at 20 wt%, and then the reaction is continuously stirred for 6 h to obtain a completely etched precursor mixed solution S1;
[0045] (3) The precursor solution S1 is placed in a vacuum filter for solid-liquid separation, and is repeatedly washed with deionized water until the pH is > 6 to obtain a wet material S2;
[0046] (4) The wet material S2 was stirred in deionized water for 1 h to obtain a mixed solution D with a solid content of 20%. The mixed solution was freeze-dried to obtain a solid solution aluminum nano-silicon material 1;
[0047] Since the dissolved aluminum phase cannot diffuse through the solid phase to the silicon surface and be digested by HCl, the dissolved aluminum nano-silicon material 1 of this embodiment 1 is subjected to plasma mass spectrometry ICP-MS test. The aluminum content measured by NaOH alkaline digestion is 4.33%, while the aluminum content measured by HCl acid digestion is 0.15%, indicating that the dissolved aluminum obtained by NaOH alkaline digestion of silicon is basically all aluminum dissolved in the silicon phase, and the aluminum solubility is about 4.18 wt.%.
[0048] The solid-solution aluminum nano-silicon material 1 of this embodiment 1 was subjected to an X-ray diffraction test, and the diffraction peak of the Si (111) crystal plane was as follows: Fig. 9As shown, compared with the standard card, it is shifted to the left by 0.068°. This is because the solid solution of aluminum into the silicon phase causes the lattice to increase; the lattice constant calculated according to the Bragg formula is 0.5436 nm, which is larger than the 0.5419 nm of the standard card.
[0049] The solid-solution aluminum nano-silicon material 1 was subjected to a compaction-conductivity test, and the test results of the change trend of its conductivity with pressure are as follows: Fig.10 As shown in Figure 2, the conductivity at 30 and 350 MPa is 1.4×10 -5 and 1×10 -3 S / cm.
[0050] The solid solution aluminum nano-silicon material 1 prepared in this embodiment was observed by scanning electron microscopy. Figure 1 The initial size of the nano-silicon is about 60 nm in diameter. The solid solution aluminum nano-silicon material 1 prepared in this embodiment is observed by TEM transmission electron microscopy-energy dispersive X-ray spectrometer EDS. Figure 2 It shows that under a magnification of 100,000 times, the silicon, aluminum and oxygen elements of nano-silicon in the 200nm area are still evenly distributed, and the aluminum element is evenly arranged along the silicon fibers, proving that the aluminum element is solid dissolved in silicon and distributed in small quantities.
[0051] The solid-solution aluminum nano-silicon material 1 negative electrode was made into a button cell with a lithium sheet as the counter electrode. The active material loading was 0.93 mg / cm 2 Conditions, the charge and discharge test was carried out at a current density of 100 mA / g, and the charge and discharge curve is as follows Figure 3 As shown, the first discharge specific capacity is 2939.2 mAh / g, the first charge specific capacity is 2471.0 mAh / g, and the first coulombic efficiency is 84.07%.
[0052] In summary, the solid solution aluminum nano-silicon material 1 prepared using Example 1 has a solid solution aluminum phase and improved conductivity, and its initial size is smaller than the critical size of silicon lithiation fragmentation (<150 nm), so that it has a higher first charge and discharge specific capacity and first coulombic efficiency.
[0053] Example 2
[0054] (1) Aluminum ingots with a purity of 99.99% and silicon ingots were fully melted at 1600°C in a ratio of 88:12, and then the alloy liquid was rapidly cooled by liquid nitrogen quenching immediately after aerosol granulation to refine the grains and dissolve aluminum at the same time, and D was selected by screening. 50 =8 μm powder.
[0055] (2) Ultrasonic dispersion of 20 g of the above-mentioned quenched aluminum-silicon alloy powder in 100 ml of 30 vol% ethanol water, ultrasonically treating at 100 Hz power for 1 h and stirring at 100 rpm for 1 h to obtain a mixed solution A, and then adding ascorbic acid to the mixed solution A to obtain a mixed solution B, wherein the mass ratio of ascorbic acid to the quenched aluminum-silicon alloy powder is 0.1:1; 240 g of 85 wt% phosphoric acid is dropwise added to 300 ml of 10 vol% ethanol water to obtain a mixed solution C, wherein the mass ratio of the quenched silicon alloy to the acid etchant is 1:10; C is poured into B to obtain a mixed solution, the concentration of phosphoric acid is controlled at 20 wt%, and then the reaction is continuously stirred for 3 h to obtain a completely etched precursor mixed solution S1;
[0056] (3) The precursor solution S1 is placed in a vacuum filter for solid-liquid separation, and is repeatedly washed with deionized water until the pH is > 6 to obtain a wet material S2;
[0057] (4) The wet material S2 was stirred in deionized water for 1 h to obtain a mixed solution D with a solid content of 20%. The mixed solution was freeze-dried to obtain a solid solution aluminum nano-silicon material 2;
[0058] Because the dissolved aluminum phase cannot diffuse through the solid phase to the silicon surface and be digested by HCl, the dissolved aluminum nano-silicon material 2 is subjected to plasma mass spectrometry ICP-MS testing. The aluminum content measured by NaOH alkaline digestion is 4.41%, while the aluminum content measured by HCl acid digestion is 0.18%, indicating that the dissolved aluminum obtained by NaOH alkaline digestion of silicon is basically all aluminum dissolved in the silicon phase, and the aluminum solubility is about 4.23 wt.%. Compared with Example 1, Example 2 has a higher aluminum solubility.
[0059] The solid solution aluminum nano-silicon material 2 of this embodiment 2 is subjected to an X-ray diffraction test. Figure 4 As shown in Figure 1, its diffraction peak shows obvious single crystal silicon peaks, without metallic aluminum phase. Its Si (111) crystal plane diffraction peak is as follows: Fig. 9 As shown, compared with the standard card, it shifts to the left by 0.1133°, which is due to the fact that aluminum is dissolved into the silicon phase, resulting in an increase in the lattice; the lattice constant calculated according to the Bragg formula is 0.5444 nm, which is greater than 0.5419 nm of the standard card. Compared with Example 1, its larger lattice constant further verifies its higher aluminum solubility, because more aluminum is dissolved into the silicon phase, resulting in an increase in the lattice.
[0060] The solid-solution aluminum nano-silicon material 2 was subjected to a compaction-conductivity test, and the test results of the change trend of its conductivity with pressure are as follows: Fig.10 As shown, the conductivity at 30 and 350 MPa is 6×10 -4 and 8×10 -3S / cm. It can be seen that compared with Example 1, the higher aluminum solid solubility in Example 2 leads to faster electron conduction, making the nano-silicon material have higher electrical conductivity.
[0061] The nano-silicon material with solid solution aluminum prepared in this embodiment was observed by scanning electron microscopy. Figure 5 The initial size of the nano-silicon is about 30 nm in diameter. Compared with Example 1, liquid nitrogen quenching can inhibit grain growth due to its higher cooling rate, thus obtaining nano-silicon with a smaller size.
[0062] The solid-solution aluminum nano-silicon anode 2 was made into a button cell with a lithium sheet as the counter electrode. 2 Conditions, charge and discharge test was carried out at a current density of 100 mA / g, and the charge and discharge curve is as follows Figure 6 As shown in Figure 1, the first discharge capacity is 3177.3 mAh / g, the first charge capacity is 2728.0 mAh / g, and the first coulombic efficiency is 85.86%. The charge and discharge cycle is carried out at a current density of 500 mA / g, and the cycle curve is shown in Figure 1. Figure 7 As shown, the capacity is 2133.9 mAh / g. After 40 cycles at this current density, the reversible specific capacity of the material is 1716.2 mAh / g, and the capacity retention rate is 80.42%.
[0063] In summary, the solid solution aluminum nano-silicon material 2 prepared using this embodiment 2 has a solid solution aluminum phase and significantly improved electrical conductivity, which makes it have a higher first charge and discharge specific capacity and first coulombic efficiency, and good cycle performance, indicating that different rapid cooling methods of aluminum-silicon alloys will affect the solid solubility of aluminum in silicon and the size of nano-silicon; and the increase in the solid solution aluminum content is conducive to the improvement of electrochemical performance.
[0064] Example 3
[0065] (1) Aluminum ingots with a purity of 99.99% and silicon ingots were fully melted at 1600°C in a ratio of 88:12, and then the alloy liquid was rapidly cooled by centrifugal disc spray to refine the grains and dissolve aluminum at the same time, and D was selected by screening. 50 =8 μm powder.
[0066] (2) Ultrasonic dispersion of 20 g of the above-mentioned quenched aluminum silicon alloy powder in 100 ml of 30 vol% ethanol water, ultrasonically treating at 100 Hz power for 1 h and stirring at 100 rpm for 1 h to obtain a mixed solution A, and then adding ascorbic acid to the mixed solution A to obtain a mixed solution B, wherein the ratio of ascorbic acid to the quenched aluminum silicon alloy powder is 0.1:1; 240 g of 85 wt% phosphoric acid is dropwise added to 300 ml of 10 vol% ethanol water to obtain a mixed solution C, wherein the mass ratio of the quenched silicon alloy to the acid etchant is 1:10; C is poured into B to obtain a mixed solution, the concentration of phosphoric acid is controlled at 20 wt%, and then the reaction is continuously stirred for 3 h to obtain a completely etched precursor mixed solution S1;
[0067] (3) The precursor solution S1 is placed in a vacuum filter for solid-liquid separation, and is repeatedly washed with deionized water until the pH is > 6 to obtain a wet material S2;
[0068] (4) The wet material S2 was stirred in deionized water for 1 h to obtain a mixed solution D with a solid content of 20%. The mixed solution was freeze-dried to obtain a solid solution aluminum nano-silicon material 3;
[0069] Because the dissolved aluminum phase cannot diffuse through the solid phase to the silicon surface and be digested by HCl, the dissolved aluminum nano-silicon material 3 was subjected to ICP-MS testing. The aluminum content was 3.70% by NaOH alkaline digestion and 0.74% by HCl acid digestion, indicating that most of the dissolved aluminum obtained by NaOH alkaline digestion of silicon is aluminum dissolved in the silicon phase, and the aluminum solubility is about 2.96 wt.%.
[0070] Scanning electron microscopy observed that the initial size of nano-silicon was about 200 nm in diameter. Compared with Examples 1 and 2, the disk spray method has a lower cooling rate, and the grains grow larger, so the size of nano-silicon is larger.
[0071] In summary, the solid solution aluminum nano-silicon material 3 prepared using Example 3 has a solid solution aluminum phase. Compared with Examples 1 and 2, Example 3 has a lower aluminum solid solubility and a larger nano-silicon size, indicating that different rapid cooling methods of aluminum-silicon alloys will affect the solid solubility of aluminum in silicon and the size of nano-silicon.
[0072] Example 4
[0073] (1) Aluminum ingots with a purity of 99.99% and silicon ingots were fully melted at 1500°C in a ratio of 88:12, and then the alloy liquid was rapidly cooled by aerosol granulation to refine the grains and dissolve aluminum at the same time, and D was selected by screening. 50 =20 μm powder.
[0074] (2) Ultrasonic dispersion of 20 g of the above-mentioned quenched aluminum silicon alloy powder in 100 ml of deionized water, ultrasonically dispersing at 100 Hz power for 0.5 h and stirring at 100 rpm for 3 h to obtain a mixed solution A, and then adding sodium ascorbate to the mixed solution A to obtain a mixed solution B, wherein the ratio of sodium ascorbate to the quenched aluminum silicon alloy powder is 0.2:1; 200 g of 37 wt% hydrochloric acid is dropwise added to 300 ml of deionized water to obtain a mixed solution C, wherein the mass ratio of the quenched silicon alloy to the acid etchant is 1:3.7; C is poured into B to obtain a mixed solution, the concentration of hydrochloric acid is controlled at 15 wt%, and then the reaction is continuously stirred for 6 h to obtain a completely etched precursor mixed solution S1;
[0075] (3) The precursor solution S1 is placed in a vacuum filter for solid-liquid separation, and is repeatedly washed with deionized water until the pH is > 6 to obtain a wet material S2;
[0076] (4) The wet material S2 was stirred in deionized water for 1 h to obtain a mixed solution D with a solid content of 40%. The mixed solution was vacuum dried to obtain a solid solution aluminum nano-silicon material 4;
[0077] Because the dissolved aluminum phase cannot diffuse through the solid phase to the silicon surface and be digested by hydrochloric acid, the dissolved aluminum nanosilicon material 4 was subjected to plasma mass spectrometry ICP-MS testing. The aluminum content measured by NaOH alkaline digestion was 4.04%, and the aluminum content measured by HCl acid digestion was 0.18%, indicating that most of the dissolved aluminum obtained by NaOH alkaline digestion of silicon is aluminum dissolved in the silicon phase, and the aluminum solubility is about 3.86 wt.%.
[0078] Scanning electron microscopy observed that the initial size of nanosilicon was about ~80 nm in diameter.
[0079] In summary, the solid-solution aluminum nano-silicon material 4 prepared by using this embodiment 4 has a solid-solution aluminum phase.
[0080] Example 5
[0081] (1) Aluminum ingots with a purity of 99.99% and silicon ingots were fully melted at 1700°C in a ratio of 88:12, and then the alloy liquid was rapidly cooled by aerosol granulation to refine the grains and dissolve aluminum at the same time, and D was selected by screening. 50 =15 μm powder.
[0082] (2) Ultrasonic dispersion of 20 g of the above-mentioned quenched aluminum-silicon alloy powder in 100 ml of water, ultrasonically treating at 100 Hz power for 1 h and stirring at 100 rpm for 1 h to obtain a mixed solution A, and then adding ascorbic acid to the mixed solution A to obtain a mixed solution B, wherein the ratio of ascorbic acid to the quenched aluminum-silicon alloy powder is 0.1:1; 240 g of 85 wt% phosphoric acid is dropwise added to 300 ml of 10 vol% ethanol water to obtain a mixed solution C, wherein the mass ratio of the quenched silicon alloy to the acid etchant is 1:10; C is poured into B to obtain a mixed solution, the concentration of phosphoric acid is controlled at 20 wt%, and then the reaction is continuously stirred for 6 h to obtain a completely etched precursor mixed solution S1;
[0083] (3) The precursor solution S1 is placed in a vacuum filter for solid-liquid separation, and is repeatedly washed with deionized water until the pH is > 6 to obtain a wet material S2;
[0084] (4) The wet material S2 was stirred in deionized water for 1 h to obtain a mixed solution D with a solid content of 20%. The mixed solution was freeze-dried to obtain a solid solution aluminum nano-silicon material 5;
[0085] Since the dissolved aluminum phase cannot diffuse through the solid phase to the silicon surface and be digested by HCl, the dissolved aluminum nano-silicon material 5 of this embodiment 5 is subjected to plasma mass spectrometry ICP-MS test. The aluminum content measured by NaOH alkaline digestion is 7.85%, while the aluminum content measured by HCl acid digestion is 0.22%, indicating that the dissolved aluminum obtained by NaOH alkaline digestion of silicon is basically all aluminum dissolved in the silicon phase, and the aluminum solubility is about 7.63wt.%.
[0086] In summary, the solid-solution aluminum nano-silicon material 1 prepared by using this embodiment 5 has a highly solid-solution aluminum phase.
[0087] Comparative Example 1
[0088] The nano-silicon material of Comparative Example 1 was subjected to an X-ray diffraction test, and the diffraction peak of the Si (111) crystal plane was as follows: Fig. 9 As shown, compared with the standard card, it is only shifted to the left by 0.0372°, indicating that the lattice state of nanosilicon has not changed much compared with the standard card; the lattice constant calculated according to the Bragg formula is 0.5430 nm, which is close to the 0.5419 nm of the standard card.
[0089] The commercial nano-silicon material was subjected to a compaction-conductivity test, and the test results of its conductivity changing with pressure are as follows: Fig.10 As shown, the conductivity at 30 and 350 MPa is 2×10 -7 and 4×10 -6 S / cm, which is much lower than that of Example 1 and Example 2. It can be seen that the solid solubility of aluminum can bring faster electronic conduction to nano-silicon, making the nano-silicon material have higher electrical conductivity.
[0090] The commercial nano-silicon anode was made into a button cell with a lithium sheet as the counter electrode. 2 Conditions, charge and discharge test was carried out at a current density of 100 mA / g, and the charge and discharge curve is as follows Figure 8 As shown, the first discharge specific capacity is 2623.7 mAh / g, the first charge specific capacity is 2083.0 mAh / g, and the first coulombic efficiency is 79.39%.
[0091] In summary, ordinary nano-silicon materials without aluminum solid solution have poor electronic conduction efficiency. The conductivity difference of about 3 orders of magnitude will make the material have low electrochemical activity and large polarization, resulting in lower first charge and discharge specific capacity and first coulombic efficiency far lower than that of nano-silicon materials with aluminum solid solution.
[0092] Comparative Example 2
[0093] (1) Select conventional aluminum-silicon alloy (99.99% aluminum ingot and silicon ingot are fully melted at 1600℃ and naturally cooled in a ratio of 88:12) and select D 50 =8 μm powder.
[0094] (2) Ultrasonic dispersion of 20 g of the aluminum-silicon alloy powder in 100 ml of 30 vol% ethanol water was performed at 100 Hz power for 1 h and stirring at 100 rpm for 1 h to obtain a mixed solution A. Ascorbic acid was then added to the mixed solution A to obtain a mixed solution B, wherein the mass ratio of ascorbic acid to aluminum-silicon alloy powder was 0.1:1; 240 g of 85 wt% phosphoric acid was dropwise added to 300 ml of 10 vol% ethanol water to obtain a mixed solution C, wherein the mass ratio of the quenched silicon alloy to the acid etchant was 1:10; C was poured into B to obtain a mixed solution, the concentration of phosphoric acid was controlled at 20 wt%, and then the reaction was continued with stirring for 3 h to obtain a completely etched precursor mixed solution S1;
[0095] (3) The precursor solution S1 is placed in a vacuum filter for solid-liquid separation, and is repeatedly washed with deionized water until the pH is > 6 to obtain a wet material S2;
[0096] (4) The wet material S2 was stirred in deionized water for 1 h to obtain a mixed solution D with a solid content of 20%. The mixed solution was freeze-dried to obtain a silicon material;
[0097] Because the solid-dissolved aluminum phase cannot diffuse through the solid phase to the silicon surface and be digested by hydrochloric acid, the silicon material was subjected to ICP-MS testing. The aluminum content measured by NaOH alkaline digestion was 0.32%, and the aluminum content measured by HCl acid digestion was 0.18%, indicating that there is basically no solid-dissolved aluminum in the silicon material.
[0098] Scanning electron microscopy observed that the initial size of the silicon material was approximately ~ 3μm in diameter.
[0099] In summary, compared with Example 2, the silicon material prepared by the non-quenching method of Example 2 has no solid-solution aluminum, and its large size (3 μm) makes it difficult to ensure that the silicon is not broken during the lithiation process (<150 nm).
[0100] Comparative Example 3
[0101] (1) Aluminum ingots with a purity of 99.99% and silicon ingots were fully melted at 1500°C in a ratio of 88:12, and then the alloy liquid was rapidly cooled by aerosol granulation to refine the grains and dissolve aluminum at the same time, and D was selected by screening. 50 =20 μm powder.
[0102] (2) Ultrasonic dispersion of 20 g of the above-mentioned quenched aluminum silicon alloy powder in 100 ml of deionized water, ultrasonically dispersing at 100 Hz power for 0.5 h and stirring at 100 rpm for 3 h to obtain a mixed solution A, and then adding sodium ascorbate to the mixed solution A to obtain a mixed solution B, wherein the ratio of sodium ascorbate to the quenched aluminum silicon alloy powder is 0.2:1; 100 g of 37 wt% hydrochloric acid is dropwise added to 300 ml of deionized water to obtain a mixed solution C, wherein the mass ratio of the quenched silicon alloy to the acid etchant is 1:1.8; C is poured into B to obtain a mixed solution, the concentration of hydrochloric acid is controlled at 15 wt%, and then the reaction is continuously stirred for 6 h to obtain a completely etched precursor mixed solution S1;
[0103] (3) The precursor solution S1 is placed in a vacuum filter for solid-liquid separation, and is repeatedly washed with deionized water until the pH is > 6 to obtain a wet material S2;
[0104] (4) Stirring the wet material S2 in deionized water for 1 h to obtain a mixed solution D with a solid content of 40%, and vacuum drying the mixed solution to obtain residual aluminum nano-silicon material;
[0105] The residual aluminum nano-silicon material of Comparative Example 3 was subjected to an X-ray diffraction test, and a strong single crystal metal aluminum phase diffraction peak appeared.
[0106] The residual aluminum nano-silicon material was subjected to plasma mass spectrometry ICP-MS testing. The aluminum content was 43.68% by NaOH alkaline digestion and 41.42% by HCl acid digestion, indicating that insufficient acid was added in comparative example 3, resulting in incomplete reaction of the metallic aluminum phase. The prepared product contained residual aluminum nano-silicon material with a high content of metallic Al phase, which could not guarantee the normal functioning of the silicon capacity.
Claims
1. A method for preparing nano-silicon material with solid solution aluminum, characterized in that: Includes the following: (1) preparing a rapidly cooled aluminum-silicon alloy by one of the following methods: aerosol granulation, liquid nitrogen quenching, centrifugal disk spraying, or belt quenching, wherein the mass proportion of the aluminum phase is 50-95%; (2) After the quenched aluminum silicon alloy is fully dispersed in the solvent L1, an antioxidant is added and dispersed, and then an acid etchant is added and continuously stirred to react to obtain a precursor mixed solution S1; (3) performing solid-liquid separation on S1, washing and collecting the solid to obtain precursor S2; (4) The precursor S2 is dried to obtain a solid solution aluminum nano-silicon material; Steps (1) to (4) are as follows: (1) Aluminum ingots and silicon ingots with a purity of 99.99% are fully melted at a mass ratio of (50-95):(50-5) above the melting point of silicon (1414°C), and then the alloy liquid is rapidly cooled by one of the following rapid cooling methods: aerosol granulation, liquid nitrogen quenching, centrifugal disk spraying, and belt quenching to dissolve aluminum and simultaneously refine the size of silicon to obtain a rapidly cooled aluminum-silicon alloy powder; (2) Dispersing the quenched aluminum silicon alloy powder in the solvent L1 to obtain a mixed solution A, and then adding an antioxidant to the mixed solution A to obtain a mixed solution B, wherein the mass ratio of the antioxidant to the quenched aluminum silicon alloy is (0-0.3):1; adding an acid etchant dropwise into the solvent L1 to obtain a mixed solution C; mixing the mixed solution C and the mixed solution B evenly, and controlling the degree of removal of the metal aluminum phase and the degree of oxidation of silicon by controlling the mass ratio of the quenched aluminum silicon alloy powder and the acid etchant, so that the mass content of the solid solution aluminum phase is 2-10%; the mass ratio of the quenched silicon alloy and the acid etchant is 1:(3-15), and the concentration of the acid etchant in the obtained mixed solution is controlled to be 15%-30%, and then continuously stirring the reaction for 3-30 h to obtain a completely etched precursor mixed solution S1; (3) The precursor solution S1 is subjected to solid-liquid separation, and is repeatedly washed with solvent L2 until the pH is greater than 6 to obtain a wet material precursor S2; (4) The wet material precursor S2 is dispersed in the solvent L3 to obtain a mixed solution D, and the mixed solution D is dried to obtain a solid solution aluminum nano-silicon material.
2. The method according to claim 1, characterized in that: The quenched silicon alloy powder obtained in step (1) is sieved and the particle size D is selected. 50 =6~80 μm.
3. The method according to claim 1, characterized in that: In step (2), the solvent L1 is a mixed solution of ethanol and deionized water, wherein the volume fraction of deionized water is 60-100%; the mass ratio of the quenched silicon alloy powder to the solvent L1 in the mixed solution A is 1:(5-50); the dispersion method is a combination of one or more of stirring and ultrasound, and the dispersion time is 0.5-10 h.
4. The method according to claim 1, characterized in that: The antioxidant in step (2) is one or a combination of sodium sulfite, ascorbic acid, isoascorbic acid, sodium ascorbate, sodium isoascorbate; the acid etchant is one or a combination of phosphoric acid, hydrochloric acid, sulfuric acid, oxalic acid, boric acid; the mass concentration of the acid etchant in the mixed solution C is 10% to 40%.
5. The method according to claim 1, characterized in that: The solid-liquid separation method described in step (3) is one or a combination of filter press, suction filtration, differential centrifugation, density gradient centrifugation, and sedimentation centrifugation; wherein the solvent L2 is an ethanol deionized water solution, wherein the volume dispersion of deionized water is 60~100%.
6. The method according to claim 1, characterized in that: The dispersion method in step (4) is a combination of one or more of stirring and ultrasound, and the dispersion time is 0.5 to 10 h; the drying method is a combination of one or more of forced air drying, vacuum drying, freeze drying, and natural evaporation drying; the solvent L3 is an ethanol deionized water solution, in which the volume fraction of water is 60 to 100%; the solid content of the mixed solution D is 20% to 60%.
7. A nano-silicon material with solid-solution aluminum prepared by the method according to any one of claims 1 to 6, wherein the mass content of the solid-solution aluminum phase is 2 to 10% and the particle size is 30 to 100 nm.
8. Use of the nano-silicon material with solid-solution aluminum as claimed in claim 7 as negative electrode material for lithium-ion secondary batteries.
9. Use of the nano silicon material with solid aluminum solution as claimed in claim 7 as a precursor for preparing silicon-based composite electrode active materials for lithium ion secondary batteries.
Citation Information
Patent Citations
Method for preparing rapid solidified fine spherical high-silicon high-wear-resistant aluminum-silicon alloy powder
CN104959620A
Porous silicon material and preparation method and application thereof, and carbon-silicon composite material and preparation method and application thereof
CN115367760A